Tobacco control in the Czech Republic - Králíková, E; Kozák, J T (Central European journal of public health, 2000)
Main points of tobacco control measures in the country are mentioned: smoking prevalence among population and health professionals (both about one third), smoking cessation availability (about 70 smoking cessation clinics), education of health professionals, both pre- and post-gradual, public-oriented actions, advertising, tobacco prices, legislation, cigarette consumption, mortality.
Keywords: příčina smrti; Smoking; Public Health Practice; veřejné zdravotnictví - praxe; odvykání kouření; Prevalence; kouření; Health Personnel; Population Surveillance; Humans; prevence kouření; Smoking Cessation; Czech Republic; Česká republika; prevalence; Advertising; mladiství; inzerce jako téma; zdravotnický personál; komunitní zdraví - plánování; Health Education; zdravotní výchova; Cause of Death; surveillance populace; Adult; výzkum; Adolescent; Smoking Prevention; dospělí; dítě; lidé; Child; Community Health Planning; Research